The wolf - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger brotherhood. Prison camp., 2021)
Rio Hernandez-Guerrero has been working undercover to bring down Caldwell's worst drug lord, the sadistic Mozart. Ordered to negotiate a massive deal with a shadowy supplier, what shows up at the meeting is nothing she expects. Lucan was locked up decades ago for the crime of being both wolven and vampire, forced to engage in drug dealing by the prison's despot. Rio and Logan both have secrets that threaten their fate as soulmates-- and their very lives. Will they win the deadly game they're playing... or will their inner natures shatter their love? -- adapted from jacket